Catalysis by design: development of a bifunctional water splitting catalyst through an operando measurement directed optimization cycle. Issue 24 (23rd May 2018) - Kornienko, Nikolay; Heidary, Nina; Cibin, Giannantonio; Reisner, Erwin
Abstract : Amorphous and bifunctional water splitting catalysts are probed with a novel spectroelectrochemical quartz crystal microbalance cell, then subsequently enhanced. Abstract : A critical challenge in energy research is the development of earth abundant and cost-effective materials that catalyze the electrochemical splitting of water into hydrogen and oxygen at high rates and low overpotentials. Key to addressing this issue lies not only in the synthesis of new materials, but also in the elucidation of their active sites, their structure under operating conditions and ultimately, extraction of the structure–function relationships used to spearhead the next generation of catalyst development. In this work, we present a complete cycle of synthesis, operando characterization, and redesign of an amorphous cobalt phosphide (CoP x ) bifunctional catalyst. The research was driven by integrated electrochemical analysis, Raman spectroscopy and gravimetric measurements utilizing a novel quartz crystal microbalance spectroelectrochemical cell to uncover the catalytically active species of amorphous CoP x and subsequently modify the material to enhance the activity of the elucidated catalytic phases. Illustrating the power of our approach, the second generation cobalt–iron phosphide (CoFePx ) catalyst, developed through an iteration of the operando measurement directed optimization cycle, is superior in both hydrogen and oxygen evolution reactivity over the previous material and is capable of overall water electrolysis at a current density of 10 mA cm −2 with 1.5 V applied bias in 1 M KOH electrolyte solution.